Analysis of Gen Z's Perception of the Services of Bank Syariah Indonesia in Danau Kerinci Subdistrict - Malbania, Yoli; Mailindra, Wiyan (Jurnal Iqtisaduna, 2025)
This study explores Generation Z’s perception of services provided by Bank Syariah Indonesia (BSI) in Danau Kerinci Barat District, a region with a predominantly Muslim population. Although BSI promotes services based on Islamic principles, its utilization among Gen Z remains limited. A qualitative approach was employed, using in-depth interviews with 20 purposively selected informants. The findings reveal that Gen Z’s perceptions are influenced by their Islamic financial literacy, digital experience through the BSI application, and religious values embedded in Islamic banking. While most participants expressed interest in profit-sharing schemes and worship-related features within the app, challenges such as limited-service accessibility and lack of product understanding persist. This study recommends strengthening Islamic financial education and enhancing the quality of digital services as key strategies to increase BSI adoption among younger generations in a sustainable manner.